(untitled) (Bulletin KNOB, 1989)
The granary at the Amsterdam Westerdoksdijk, designed by architect Klinkhamer, recently became out of use by the new destination of the Westerdok area as western emphasis in the new harbour-project. The threatening demolition of the granary is reason to evaluate the introduction of this building type in Holland and the granaries built by Klinkhamer. The horizontal packing up of cereals in warehouses has in Europe and America during the second half of the 19th century been replaced by vertical storage in tubes (silo’s), joined to a granary with mechanical appliance for vertical transport by ladders (elevators) and horizontal mostly by conveyor belts. Also drying and purifying was driven by a steam engine, while after weighing load and discharge of the cargo-boats transport again passed by the elevator system. Technical problems like the extreme heaviness of such granaries slowed down the introduction of this type. The American ’sillon-system’ first introduced in Germany in the 1880’s, the first Dutch granary was built at Delft by architect Zieren in commission of J. C. Marken for his ’Gist en Spiritus’ factories (1885-86). Educated at the Polytechnische School Delft Jacob F. Klinkhamer (1854-1929) must have known about this project when he had to design a granary for J. Reynvaan at Amsterdam (1885). The mechanical installation delivered by specialist firm G. Luther from Braunschweig, Klinkhamer’s granary is a boxlike building with saddle-roof, the tower containing the installation for vertical transport. In 1888 Klinkhamer and Reynvaan pleaded for the building of more granaries in Amsterdam as ’last entrenchment’ of Holland to be able to feed her population in times of war. The added design for a large stone granary at the harbour front already largely is the granary for the Delftsche Distilleerderij and in 1895 for the bradfactory ’Holland’ at Amsterdam. By his contacts with the town councilors R. W.J.C. van den Wall Bake and J.Ph. Korthals Altes (who pleaded western expansion of the harbour) and his experience with this building type Klinkhamer was almost automatically chosen to build a large granary in the western harbour area (1896). Technical problems solved by engineer A.L. van Gendt Klinkhamer’s granary Korthals Altes combines classical building up with functional division. The purification-building in front of instead of between the silo’s (like G. Luther’s), this granary resembles a granary designed by the firm Ulrich at Boedapest. In 1899 Klinkhamer became Professor in functional architecture at the Polytechnische School Delft, teaching medieval and functional architecture. Still no suitable design principles developed for functional architecture, one used the rudiments of Gothic as most rational and constructive style. Studying this style one could accomplish elementary skills to solve actual problems. Klinkhamer’s interpretation a.o. derived from Viollet-le-Duc and Cuypers favoured a ’dechristianized’ Gothic and besides Early Gothic or rather Romanesque style. At home and abroad the forms of medieval civil architecture like castles and city gates were applied at functional buildings. The expression of ’character’ of a building as one of the most important elements of contemporary architectural thinking this choice seems logical. The military association of 1888 still actual at the Korthals Altes granary of 1896, the closeness of the building, the austere ornaments with medieval elements, the constructive articulation and balanced proportions are all means to indicate ’character’. It is this same ’character’ of the building, which retards a redevelopment plan and threatens the granary with demolition.